COVID-19–Related Internet Search Patterns Among People in the United States: Exploratory Analysis - Shen, Tony S (J Med Internet Res, 2020)
BACKGROUND: The internet is a well-known source of information that patients use to better inform their opinions and to guide their conversations with physicians during clinic visits. The novelty of the recent COVID-19 outbreak has led patients to turn more frequently to the internet to gather more information and to alleviate their concerns about the virus. OBJECTIVE: The aims of the study were to (1) determine the most commonly searched phrases related to COVID-19 in the United States and (2) identify the sources of information for these web searches. METHODS: Search terms related to COVID-19 were entered into Google. Questions and websites from Google web search were extracted to a database using customized software. Each question was categorized into one of 6 topics: clinical signs and symptoms, treatment, transmission, cleaning methods, activity modification, and policy. Additionally, the websites were categorized according to source: World Health Organization (WHO), Centers for Disease Control and Prevention (CDC), non-CDC government, academic, news, and other media. RESULTS: In total, 200 questions and websites were extracted. The most common question topic was transmission (n=63, 31.5%), followed by clinical signs and symptoms (n=54, 27.0%) and activity modification (n=31, 15.5%). Notably, the clinical signs and symptoms category captured questions about myths associated with the disease, such as whether consuming alcohol stops the coronavirus. The most common websites provided were maintained by the CDC, the WHO, and academic medical organizations. Collectively, these three sources accounted for 84.0% (n=168) of the websites in our sample. CONCLUSIONS: In the United States, the most commonly searched topics related to COVID-19 were transmission, clinical signs and symptoms, and activity modification. Reassuringly, a sizable majority of internet sources provided were from major health organizations or from academic medical institutions.